1996
DOI: 10.1103/physrevb.54.4488
|View full text |Cite
|
Sign up to set email alerts
|

Observation of laser-induced microscale knotted and unknotted vortex filaments on vaporizing tantalum surface

Abstract: surface superheating on a ns time scale is connected with the formation of a spinodal fluid which decomposes into a gaseous phase through microexplosions, generating vortex filament structures on the vaporizing surface. Vortex filaments associated with the Reynolds number Reϳ10 3 -10 4 are organized into regular, quasiregular, or chaotic structures. Homotopic operations transfer these structures into irreducible ones of a simple closed-loop type, showing that all of them are embedded in a three-dimensional tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The studies performed by our group in the regime of transition from planar-to-volume vaporization, at "10 ns, have shown the spontaneous formation of open-and closed-loop vortex "laments, showing various levels of the organization complexity (Lugomer 19961998a,b). Continuing the series of studies, this paper deals with generation of the microscale vortex rings and their interactions, especially with collision, reconnection and breaking, as a non linear and nonequilibrium process with strong dissipative character.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The studies performed by our group in the regime of transition from planar-to-volume vaporization, at "10 ns, have shown the spontaneous formation of open-and closed-loop vortex "laments, showing various levels of the organization complexity (Lugomer 19961998a,b). Continuing the series of studies, this paper deals with generation of the microscale vortex rings and their interactions, especially with collision, reconnection and breaking, as a non linear and nonequilibrium process with strong dissipative character.…”
Section: Introductionmentioning
confidence: 98%
“…They travel in all directions and being re#ected from the sidewalls (of the small sample) they reverberate thorugh the sample, causing the interaction with surface hydrodynamic structures (vortex rings). The momentum transferred from the shock wave to the vortex ring causes its collision with other rings, the result of which is their interaction (Lugomer 1996(Lugomer , 1998Lugomer & Maksimovic 1997.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A SERIES OF STUDIES OF SELF-ORGANIZATION (SO) of various types of entities in laser}matter interaction (LMI), like droplets (Lugomer & MaksimovicH 1996), vortex "laments (Lugomer 1996(Lugomer , 1998Lugomer & MaksimovicH 1997), and bubbles (Lugomer & MaksimovicH 1999) has shown that various types of patterns of every entity can be generated. It has also been shown that these patterns change not only in the morphological sense, but also in the sense of topological complexity, depending (for "10 ns laser pulse) on laser power density Q N .…”
Section: Introductionmentioning
confidence: 99%